2011
DOI: 10.1177/2041297510393793
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of cutting force and temperature of end-milling Ti–6Al–4V with different minimum quantity lubrication (MQL) parameters

Abstract: Different parameters (air pressure, quantity of minimum quantity lubrication (MQL) oil, position of nozzle, etc.) of an MQL system have different effects on the milling force and milling temperature. The cutting force and cutting temperature, which are closely related to lubrication and coolant, play significant roles in improving/reducing the cutting quality of a workpiece and extending/shortening the tool life. The present work investigates experimentally the effects of different MQL parameters (air pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(47 citation statements)
references
References 10 publications
4
42
0
1
Order By: Relevance
“…Increase in air pressure causes a decrease in droplet diameter and thus helps the aerosol to penetrate in the tool-chip interface. However, beyond a certain value of air pressure, the aerosol effect starts detoriating due to spring back of high speed droplets from the chip tool interface (Liu et al, 2011). The air pressure in MQL varies from 4 to 6.5 kgf/cm 2 (Silva et al, 2005), so a value close to the mid level of this range i.e.…”
Section: Nozzle Related Parametersmentioning
confidence: 99%
“…Increase in air pressure causes a decrease in droplet diameter and thus helps the aerosol to penetrate in the tool-chip interface. However, beyond a certain value of air pressure, the aerosol effect starts detoriating due to spring back of high speed droplets from the chip tool interface (Liu et al, 2011). The air pressure in MQL varies from 4 to 6.5 kgf/cm 2 (Silva et al, 2005), so a value close to the mid level of this range i.e.…”
Section: Nozzle Related Parametersmentioning
confidence: 99%
“…Tool wear values were found to be about 1.6% less with feed direction in MQL compared to 6.15% with jet cooling. Liu et al [42] found that an MQL spraying nozzle position of 135 • and a spraying distance of 25 mm helped to reduce cutting temperature by 2.5 and 20 • C compared to 90 • nozzle angle and 45 mm spraying distance, respectively. Another recent work by [43] has investigated the effect of a new sensor-based cutting fluid supply system on machined surface quality using minimum quantity fluid MQF cooling.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the proximity of the nozzle positioned at an angle of 15°from the tool-workpiece contact point contributed in minimising the fluid particle dispersion caused by tool rotation, which allowed them to adhere to the tool and workpiece surfaces effectively and to persist in working as a lubricant in the machining zone. Conversely, at the nozzle positions of 45°or 60°, more cutting fluid particles are driven away from the tool surface whilst the cutting tool rotates in a cyclic loop process [66]. In addition, nozzle placement at an angle of 45°or 60°against feed direction tends to offer enough space to assist in chip evacuation and this helped to minimise the interference between the impinging jet and the removed chip, which led to better lubricating and cooling ability and consequently improved machined surfaces.…”
Section: Tool Flank Wearmentioning
confidence: 99%
“…According to Bernoulli's equation (Eq. 4) [66], the hydraulic head (h) (where in this case, the impinging distance is equal to the hydraulic head) has an effect on jet velocity, and this consequently affected fluid penetration efficiency. The cutting fluid jet velocity (V j ) increases as the impinging distance decreases.…”
Section: Tool Flank Wearmentioning
confidence: 99%
See 1 more Smart Citation